Analyzing The Role of Digital Entrepreneurial Mindset (DEM) In Enhancing Msme Competitiveness: A Case Study of Sanlash Beauty Salon - Sidik, Sanita Abdurahim; Rahmat, Taufiq; Syahrir, Annisa Martina (KarismaPro, 2025)
The digital transformation of micro, small, and medium enterprises (MSMEs) has emerged as a critical factor for maintaining competitive advantage in contemporary business environments. This qualitative case study investigated how Digital Entrepreneurial Mindset (DEM) enhances competitiveness in Sanlash Beauty, a beauty salon MSME in Bandung, Indonesia. The research employed in-depth interviews with salon owners, managers, and six customers, complemented by participant observation and document analysis conducted between May and June 2024. Results demonstrated that DEM implementation significantly improved service innovation through digital reservation systems and social media integration, enhanced customer feedback responsiveness via multi-platform communication channels, and facilitated digital payment adoption with 70% customer utilization rate. Service innovation showed mixed adoption patterns, with 70% of customers embracing digital services while 30% maintained conventional approaches. Customer satisfaction increased through personalized service delivery, rapid feedback response mechanisms achieving 24-hour response times, and flexible payment options including e-wallets and bank transfers. Implementation barriers included system errors in digital payments, promotional content management challenges, and staff adaptation difficulties requiring ongoing training programs. The study revealed that DEM serves as a fundamental framework enabling MSME competitiveness enhancement through operational efficiency improvements and customer experience optimization. These findings contribute theoretical insights into digital transformation strategies for traditional service sectors and provide practical frameworks for MSME digital adoption initiatives.